Dual pH and oxidation-responsive nanogels crosslinked by diselenide bonds for controlled drug delivery. (28th September 2016) - Cheng, Xinfeng; Jin, Yong; Qi, Rui; Fan, Wuhou; Li, Hanping; Sun, Xiaopeng; Lai, Shuangquan
Abstract: A new diselenide crosslinked polyurethane nanogel was developed, which could respond to pH change and oxidaiton condition. Firstly, PEGylated polyurethane (MPEG-PUBM-MPEG) containing tertiary amino and Br groups was prepared, which can assemble into micelles in aqueous solution. Then the nanogels with diselenides crosslinked polyurethane (PU) core and hydrophilic PEG shell were prepared using sodium diselenide (Na2 Se2 ) as a crosslinking agent to react with the Br groups in the PUBM block. The resultant nanogels exhibited enhanced colloidal stability relative to the non-crosslinked micelles, which have a spherical morphology with a diameter about 110–120 nm. Interestingly, the nanogels displayed a pH-induced swelling and oxidation-triggered dissociation behaviors, which can efficiently load indomethacin (IND) drugs and showed an inhibited premature release behavior as compared to the non-crosslinked micelles. An accelerated release behavior at pH 5.0 (54% in 24 h) and a burst release under oxidation condition (95% in 20 h) were observed for the nanogels, indicating their dual pH and oxidation-triggered release behaviors. Considering their enhanced stability, pH-induced swelling and oxidation-triggered degradation characteristics, the diselenide crosslinked nanogels can serve as a potential system for controlled drug delivery. Graphical abstract: Novel diselenides core-crosslinked polyurethane nanogels with enhanced colloidal stability were developed as dual-stimuli triggered drug delivery vehicles, which showed distinct pH-induced swelling process and oxidation-triggered dissociation behavior. Highlights: Diselenides core-crosslinked polyurethane nanogels were developed. The nanogels showed distinct pH-induced swelling process and oxidation-triggered dissociation behavior. These diselenide-crosslinked nanogels demonstrated excellent stability with inhibited drug release behavior. The nanogels showed the dual-stimuli triggered release behaviors.